Iron-Containing Abdominal Pathologies: Exploiting Magnetic Susceptibility Artifact on Dual-Echo Gradient-Echo Magnetic Resonance Imaging. Issue 2 (March 2019) - Thomas, Aaron J.; Morani, Ajaykumar C.; Liu, Peter S.; Weadock, William J.; Hussain, Hero K.; Elsayes, Khaled M.
Abstract : Abstract: A multitude of pathologic entities involve abnormal iron deposition in the abdomen. These lesions demonstrate decreased signal on longer magnetic resonance sequences with longer echo time due to T2* effect. Dual-echo gradient-echo sequences demonstrate increased susceptibility artifact with longer echo sequences. In this article, the spectrum of iron-containing abdominal pathologies is illustrated, with their characteristic distributions. Included is a brief discussion of the physics of magnetic resonance imaging of iron-containing lesions.